2019
DOI: 10.4314/ijbcs.v12i6.28
|View full text |Cite
|
Sign up to set email alerts
|

Seed bank dynamics and restoration of Ibodi monkey forest reserve, Southwestern Nigeria

Abstract: Ibodi Monkey forest reserve (IBMFR) is known for its rich flora and fauna, mainly contributed by regrowth forest species. However, intensive anthropogenic interferences such as agriculture, illegal mining and selective exploitation over a large extent of these ecosystems in the past years have led to a serious depletion of forest's diversity. Consequently, restoration of IBMFR has become a high priority for ecological management of forest. The distribution of soil seed bank in three different physiognomies, (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
0
0
Order By: Relevance
“…Also, seeds shifted into deep soil depth would be able to germinate but failed to emerge in the soil surface (lethal germination) (Gardarin et al, 2010). This is in line with Odeleye et al (2018) who reported on the position of the seeds in the soil as a main factor for successful germination and emergence.…”
Section: Discussionsupporting
confidence: 80%
“…Also, seeds shifted into deep soil depth would be able to germinate but failed to emerge in the soil surface (lethal germination) (Gardarin et al, 2010). This is in line with Odeleye et al (2018) who reported on the position of the seeds in the soil as a main factor for successful germination and emergence.…”
Section: Discussionsupporting
confidence: 80%
“…This might be due to the trend of seasonal modes of seed production, dispersal and storage in the soils of the study sites. This can be further corroborated with the report of Odeleye et al (2018) who observed that seasonal variation in seed density at sites of varying physiognomy might be related to climatically seasonal changes as seed of some species show strong seasonal shifts in density.…”
Section: Aliens Indigenoussupporting
confidence: 88%